2020
DOI: 10.1038/s41433-020-0939-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SARS-CoV-2 receptor ACE2 and TMPRSS2 in human primary conjunctival and pterygium cell lines and in mouse cornea

Abstract: Purpose To determine the expressions of SARS-CoV-2 receptor angiotensin-converting enzyme 2 (ACE2) and type II transmembrane serine protease (TMPRSS2) genes in human and mouse ocular cells and comparison to other tissue cells. Methods Human conjunctiva and primary pterygium tissues were collected from pterygium patients who underwent surgery. The expression of ACE2 and TMPRSS2 genes was determined in human primary conjunctival and pterygium cells, human ocular and other tissue cell lines, mesenchymal stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
206
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(221 citation statements)
references
References 40 publications
9
206
0
6
Order By: Relevance
“…Human epithelial colorectal adenocarcarcinoma cells (Caco-2) and human lung cancer cells (Calu-3) were maintained in DMEM, 20% FCS, 1% NEAA, 1% P/S. VeroE6/TMPRSS2 cells were obtained from the Centre for AIDS Reagents (National Institute for Biological Standards and Control) (Matsuyama et al, 2020; Nao et al, 2019), and maintained in DMEM, 10% FCS, 1% NEAA, 1% P/S, 1 mg/ml Geneticin (G418). Air liquid interface Human airway epithelial cells (HAEs) were purchased from Epithelix and maintained in Mucilair cell culture medium (Epithelix).…”
Section: Methodsmentioning
confidence: 99%
“…Human epithelial colorectal adenocarcarcinoma cells (Caco-2) and human lung cancer cells (Calu-3) were maintained in DMEM, 20% FCS, 1% NEAA, 1% P/S. VeroE6/TMPRSS2 cells were obtained from the Centre for AIDS Reagents (National Institute for Biological Standards and Control) (Matsuyama et al, 2020; Nao et al, 2019), and maintained in DMEM, 10% FCS, 1% NEAA, 1% P/S, 1 mg/ml Geneticin (G418). Air liquid interface Human airway epithelial cells (HAEs) were purchased from Epithelix and maintained in Mucilair cell culture medium (Epithelix).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, four studies [ 6 , 10 – 12 , 14 ] reported 17 COVID-19 patients whose initial symptom was conjunctivitis/conjunctival congestion ( Figure 3 ). The pooled prevalence rate was 1% (95% CI: 1%-4%).…”
Section: Resultsmentioning
confidence: 99%
“…During the SARS pandemic, a study confirmed that ACE2 was a functional receptor for SARS-CoV [ 21 ]. A recent study revealed that ACE2 is expressed in human cornea tissues and that a high and consistent expression of ACE2 in the cornea poses a high potential for infection by SARS-CoV-2 [ 10 , 11 ]. ACE2 expression has also been reported in human aqueous humor [ 22 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…To study the effects of TRIM28 on ACE2 expression, TRIM28 siRNAs were transfected into A549 cell, a commonly used cell line model for type II pulmonary epithelial cells expressing ACE2 [20,21]. We observed that TRIM28 knockdown strikingly increased the expression of ACE2 ( Figure 1A).…”
Section: Knockdown Of Trim28 Increases Pseudotyped Sars-cov-2 Cell Enmentioning
confidence: 94%